MENINGKATKAN MOTORIK HALUS MELALUI MOZAIK BAGI ANAK TUNAGRAHITA SEDANG KELAS I DI SLB GEMA INSANI PADANG - GUSTIVA -; Zulmiyetri -; Armaini - (Jurnal Penelitian Pendidikan Khusus, 2018)
Abstract. This research was done due tu student’ stiff motors in doing classroom activities. It happened because their fine motors’ ability was still low. This research aimed at improving student’ fine motors by using mosaic for the mental retarded students at class D.I.This design of the research was class action research. The research was done under the collaboration of the homeroom teacher and two students (HF and PT).  The subjects of the research was two mental retarded students of class D.I at SLB Gema Insani Padang. Data were obtained from observation, test, and documentation. They were analyzed by using both qualitative and quantitative approaches.The results of analysis showed that: 1) the learning process by using mosaic (sticking dry banana leaves) in improving students’ fine motors was done in two cycles. Cycle I was done in seven meetings and cycle II was in five meetings. Each cycle consisted of the planning stage, the application stage, the observation stage, and the reflection stage. 2) HF’s learning outcame improved from 43.5% in the assessment stage to 87% in cycle I dan 97.8% in cycle II. Meanwhile PT’s learning outcome improved from 37% in the assessment stage to 78.3% in cycle I improve the mental retarded students’ fine motors. Thus, it is sugested to the school, the teachers and the future researchers to use mosaic in developing mental retarded students’ fine motors.